Decentralization matters - Differently organized mental health services relationship to staff competence and treatment practice : the VELO study - Olstad, Reidun; Bjorbekkmo, Svein; Myklebust, Lars H.; Sørgaard, Knut; Molvik, Stian; Nymann, Asle (BioMed Central, 2009)
Background: The VELO study is a comparative study of two Community Mental Health Centres (CMHC) in Northern Norway. The CMHCs are organized differently: one has no local inpatient unit, the other has three. Both CMHCs use the Central Mental Hospital situated rather far away for compulsory and other admissions, but one uses mainly local beds while the other uses only central hospital beds. In this part of the study the ward staffs level of competence and treatment philosophy in the CMHCs bed units are compared to Central Mental Hospital units. Differences may influence health service given, resulting in different treatment for similar patients from the two CMHCs. Methods: 167 ward staff at Vesterålen CMHCs bed units and the Nordland Central Mental Hospital bed units answered two questionnaires on clinical practice: one with questions about education, work experience and clinical orientation; the other with questions about the philosophy and practice at the unit. An extended version of Community Program Philosophy Scale (CPPS) was used. Data were analyzed with descriptive statistics, non-parametric test and logistic regression. Results: We found significant differences in several aspects of competence and treatment philosophy between local bed units and central bed units. CMHC staff are younger, have shorter work experience and a more generalised postgraduate education. CMHC emphasises family therapy and cooperation with GP, while Hospital staff emphasise diagnostic assessment, medication, long term treatment and handling aggression. Conclusion: The implications of the differences found, and the possibility that these differences influence the treatment mode for patients with similar psychiatric problems from the two catchment areas, are discussed.